HUBUNGAN LOW BACK PAIN, STRES KERJA, DAN BEBAN KERJA TERHADAP PRODUKTIFITAS KERJA DOSEN DI UNIVERSITAS PERINTIS INDONESIA TAHUN 2022 (Al Dzahab, 2023)
Purpose: The purpose of this study was to analyze the relationship between Low Back Pain, work stress and workload on lecturers' work productivityDesign/methodology/approach: Research methodology, quantitative research, using a cross sectional approach, multiple logistic analysis with prediction type. The population in this study were 103 lecturers. The sampling technique used is total sampling, by using 71 samples. The instruments were used the Nasa TLX Questionnaire for mental workload, pain and distress scale questionnaire for LBP, and work productivity questionnaire. Data processing using SPSS 22 Findings: The results of the analysis can be concluded that there is no significant relationship between the independent and dependent variables. Low Back Pain, Working  stress and workload were confounding factor, as risk factor for work  productivity. The independent variable has a P value > 0.05. OR variable low back pain = 4.00 Variable mental workload OR = 0.96 Variable work stress OR =354139403.479Research implications: It is necessary to organize working room, a more comfortable and ergonomic lecturer's work attitude, stress management and workload for prevention.